The Benefits and Challenges of Digital Transformation in Industry 4.0 (Global Journal of Management and Business Research, 2019)
The development of digital technologies has been promoting a real transformation in the lives of people and businesses in recent years. This movement has been called Digital Transformation. It intensified in the mid-2000s when many companies began a move to adapt their business infrastructure to the new digital age, benefited from the average price reduction of technology components, increased computing performance and global connectivity. In the manufacturing industry, a similar move, albeit a little late, has been carried out by the development of Industry 4.0 or, as some prefer to call it, smart factories. This article presents a vision of the digital transformation in industry, emphasizing the benefits and key challenges, from the analysis of 9 relevant publications published between 2005 and 2014. Its content will be especially important for those who are beginning their research on this topic. but whose practical implications can already be felt in our daily lives. Throughout the text, we discuss the breadth and importance of the Internet of Things and cloud computing for Industry 4.0, the applications and the importance of identification and tracking technologies, wired and wireless sensors, big data, communication protocols and distributed intelligence, the new role of IT strategy in manufacturing organizations, the impacts of new modes of production on organizational structures and the foundations of work, and the possibilities for generating, extracting and analyzing large volumes of data from connected machines in a collaborative community.
Keywords: smart factories; manufacture; technological development; digitization; digital strategy